Morphine produces better thermal analgesia in young Huntington mice and are associated with less neuroinflammation in spinal cord. Issue 1 (26th October 2020) - Liu, Yuan-Yuarn; Lin, Ya-Chi; Hsiao, Hung-Tsung; Wang, Jeffery Chi-Fei; Liu, Yen-Chin
Abstract : Background: Huntington's disease (HD) is an inherited disease characterized by both mental and motor dysfunctions. Our previous studies showed that HD mice demonstrate a diminished pain response. However, few studies have focused on the relationship between HD and morphine analgesia. The purpose of this study is to investigate and compare the analgesic effects of morphine in HD and wild-type (WT) mice. Methods: We used clinically similar transgenic HD mice (7-10 weeks of age with motor dysfunction at 8-9 mo of age) carrying a mutant Huntington CAG trinucleotide repeats to evaluate morphine analgesia. The morphine (10 mg/kg subcutaneously) analgesia was evaluated with a tail-flick in hot water (52°C). Mice spinal cords were harvested at the end of the analgesia studies. An immunofluorescence assay and western blotting were used to identify changes in the cells and cytokines. Results: Our data demonstrate that preonset young HD mice exhibited a better analgesic response to morphine than the WT mice. Western blotting and an immunohistological examination of the lumbar spinal cord tissue indicated less activation of glial cells and astrocytes in the HD mice compared with the WT mice. The production levels of tumor necrosis factor α and interleukine-1β were also lower in the young HD mice. Conclusion: Our data demonstrate better morphine analgesic and less pain-related cytokine responses at the spinal cord level for HD mice. Further studies are needed to determine the morphine analgesia mechanism in HD.